2015
DOI: 10.2147/oajsm.s33605
|View full text |Cite
|
Sign up to set email alerts
|

Role of nutrition in performance enhancement and postexercise recovery

Abstract: A number of factors contribute to success in sport, and diet is a key component. An athlete’s dietary requirements depend on several aspects, including the sport, the athlete’s goals, the environment, and practical issues. The importance of individualized dietary advice has been increasingly recognized, including day-to-day dietary advice and specific advice before, during, and after training and/or competition. Athletes use a range of dietary strategies to improve performance, with maximizing glycogen stores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
0
9

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 99 publications
2
105
0
9
Order By: Relevance
“…Using nutritional supplements was most frequently reported as the most beneficial recovery strategy when participants' responses were considered collectively, potentially reflecting an awareness amongst participants that basic nutrition such as replenishing energy and repairing tissue stores is a key aspect of optimising postexercise recovery [12]. However, participants were only questioned regarding their supplementation rather than other nutritional strategies which they may employ, limiting the potential relevance of this finding.…”
Section: Reasons For Using Recovery Strategiesmentioning
confidence: 99%
“…Using nutritional supplements was most frequently reported as the most beneficial recovery strategy when participants' responses were considered collectively, potentially reflecting an awareness amongst participants that basic nutrition such as replenishing energy and repairing tissue stores is a key aspect of optimising postexercise recovery [12]. However, participants were only questioned regarding their supplementation rather than other nutritional strategies which they may employ, limiting the potential relevance of this finding.…”
Section: Reasons For Using Recovery Strategiesmentioning
confidence: 99%
“…Consequently, the aim of this study was to investigate the effect of BCAA supplementation on recovery from a sport-specific damaging bout of resistance exercise in trained volunteers. In this way number of researchers have shown that the addition of branched-chain amino acids activates the synthesis and reduces the breakdown of the muscle protein [3,8,12,23,29], but the data of other authors do not confirm these findings [6,7,19,21,28]. In this regard, the purpose of this study was to study the effect of protein supplements (whey protein) on the process of rehabilitation for muscle injuries caused by physical stress.…”
Section: Introductionmentioning
confidence: 98%
“…1,2 Individuals adopting a diet with low energy availability may develop the relative energy deficiency in sport syndrome, known to compromise protein synthesis, bone health, and the functioning of the cardiovascular, gastrointestinal and immunological systems. 3,4 Furthermore, low energy availability decreases muscle glycogen storage, which may cause fatigue and increased perception of effort, affecting sports performance. 1,4 Dietary strategies vary according to the sports modalities, personal goals and food preferences.…”
Section: Introductionmentioning
confidence: 99%